Damage Identification and Performance Assessment of Regular and Irregular Buildings Using Wavelet Transform Energy - Mosbeh R. Kaloop; Jong Wan Hu (Advances in Materials Science and Engineering)
This study investigates a novelty wavelet application for damage detection of regular and irregular building structures under seismic load effects. The energy of wavelet transform and correlation coefficient are used to detect the performance of the damaged building. The simple 3D regular and irregular simulation (finite element model) models of a building are designed to verify the methods’ uses and optimum applications. The obtained results reveal that the energy of Discrete Wavelet Transform (DWT) shows significantly higher performance than the energy of Continuous Wavelet Transform (CWT) in detecting the damage of the building, and the performance of irregular buildings appeared suitable for use in the seismically active areas. In addition, it can be concluded that the correlation coefficient can be applied to study the effects of damage and the safety of structures.